Evaluasi Kesesuaian Potensi Lahan Pertanian Pangan Berkelanjutan Terhadap Rencana Tata Ruang Wilayah - Rachman Andriawan; Rochmat Martanto; Slamet Muryono (Tunas Agraria, 2020)
Agriculture is a strategic sector that has an important role in the economy and food security. However, from time to time agricultural land is increasingly eroded due to land conversion. This study aims to map the potential for LP2B in Magelang city as well as map the suitability of LP2B potential. The method used in this study is qualitative with a spatial approach to the determinant of LP2B potential variables by land use of paddy fields to produce LP2B Potential Maps in Magelang City and their conformity with the RTRW. Of all paddy fields covering 215,817 ha, 52.68% has high potential (K1); 41.7% potential (K2); and 5.62% less potential (K3). Paddy fields has conformity with LP2B and agricultural area K1: 37.59%; K2: 23.64%; K3: 4.36%. Paddy fields has discrepancy K1: 15.1%; K2: 18.06%; K3: 3.36%.